2004
DOI: 10.1590/s1516-35982004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Valores de composição química e energética de alguns alimentos para aves

Abstract: RESUMO -O experimento foi realizado com o objetivo de determinar a composição química e os valores energéticos de oito alimentos (milho grão, milho pré-cozido I e II, farelo de canola, plasma sangüíneo, farinha de vísceras, glicose e amido de milho) para aves. Para determinação dos valores de energia metabolizável aparente (EMA) e aparente corrigida (EMAn), foi utilizado o método tradicional de coleta total de excretas, com 400 pintos de corte, machos e fêmeas, de 21 dias de idade. O delineamento experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
2
3
2
1
Order By: Relevance
“…Silva (2006) 3 ) density as determined in a gravity table, and concluded that higher density corn has higher energy value due to its higher starch content. Average crude protein values ranged from 7.2 to 9.1%, with an average 8.1%, similarly to those reported by Rostagno (2005) and Rostagno (2011), of 8.6 and 7.9%, respectively, but higher than those obtained by Agostini et al (2004), who obtained 7.3%, which is close to the minimum value obtained in the present study. The CP values reported by Rodrigues et al (2001) and Freitas et al (2005) were close (9.3 and 9.8%, respectively) to the maximum values obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Silva (2006) 3 ) density as determined in a gravity table, and concluded that higher density corn has higher energy value due to its higher starch content. Average crude protein values ranged from 7.2 to 9.1%, with an average 8.1%, similarly to those reported by Rostagno (2005) and Rostagno (2011), of 8.6 and 7.9%, respectively, but higher than those obtained by Agostini et al (2004), who obtained 7.3%, which is close to the minimum value obtained in the present study. The CP values reported by Rodrigues et al (2001) and Freitas et al (2005) were close (9.3 and 9.8%, respectively) to the maximum values obtained in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Ether extract differences were observed, with values ranging between 3.4 and 5.1% (average of 4.0%) which are higher than those reported by Rostagno et al (2005), Freitas et al (2005), and Rostagno (2011) (3.5, 3.5, and 3.6%, respectively), but lower than that reported by Agostini et al (2004), of 4.7%.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Dale et al (1993), in 22 samples of by-product meal, observed that the lowest value determined from ether extract was 18.3%, and the highest was 39.4%. The real metabolizable energy values determined for these by-product meals were 3,626 and 5,247 kcal/kg, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Before this procedure to nullify the effects of humidity in the byproduct meal, the correction for the same dry basis of crude protein, ether extract, mineral matter, gross energy, calcium and phosphorus content, by adjusting the values to 92% of dry matter, was carried out, as suggested by Dale et al (1993).…”
Section: Methodsmentioning
confidence: 99%